“The Worst Part Was Coming Back Home and Feeling Like Crying”: Experiences of Lesbian, Gay, Bisexual and Trans Students in Portuguese Schools - Gato, Jorge; Leal, Daniela; Moleiro, Carla; Fernandes, Telmo; Nunes, Diogo; Marinho, Inês; Pizmony-Levy, Oren; Freeman, Cody (Frontiers in Psychology, 2020)
Portugal is one of the most egalitarian countries in Europe in terms of lesbian, gay, bisexual, transgender, and intersex (LGBTI) individuals’ legal rights. However, regarding education Portugal still lacks specific policies, plans and interventions to protect LGBTI students. To assess the perceptions of self-identified LGBTI youth regarding their school context, a total of 663 participants (aged from 15 to 20 years old) filled in an on-line questionnaire about their school climate. One hundred and forty six of them answered an open-ended question about their personal experiences. A thematic analysis of these answers was conducted, and four main categories were identified: (i) victimization; (ii) coming out experiences; (iii) support networks; and (iv) demands. Most participants reported experiences of discrimination, and several sources of prejudice were identified. Furthermore, participants also recognized a lack of LGBTI information in school curriculum and made several demands. Besides inclusive laws, we suggest that the safety and the well-being of LGBTI youths in Portuguese schools depend upon others measures, such as teacher and school staff training, curricula inclusive of LGBTI diversity, and local strategies, such as Gay-Straight Alliances.